Analisis Pengaruh Manajemen Keuangan terhadap Kinerja Perusahaan di Sektor Keuangan: Analysis of the Influence of Financial Management on Company Performance in the Financial Sector - Fika Wardah Al Musyafa'ah; Lailatul Zahra; Dinda Khalimatus Sya'diyah; Malinda Dwi Hanjani Setyo; M. Asrofi Zamzammi; M. Akbar Al-Kahfi (TALI JAGAD JOURNAL, 2026)
Financial management plays a crucial role in maintaining the stability and effectiveness of company operations, particularly in the financial sector, which demands careful fund management. This study aims to analyze the effect of financial management on company performance in the financial sector. Using a descriptive quantitative approach, this study involved 30 respondents consisting of students and MSME practitioners with relevant knowledge in finance and business management. Primary data collection was conducted using a Likert scale questionnaire, which was then processed through simple linear regression analysis using SPSS version 25 software. The findings indicated that financial management exerts a positive and significant influence on firm performance, evidenced by a calculated t value of 3.742 > t table value of 1.697, and a significance level of 0.001, < 0.05. This finding confirms that the application of good financial management principles can improve the efficiency, liquidity stability, and profitability of companies in the financial sector.